Development of Low-Fat Sambal Pecel Powder with Combination of Red Bean, Cowpea and Green Bean Substitutions - Lathifah Kusuma Wardani; Hevenia Arma; Zeni Kurnia; Reza Widyasaputra (G-Tech: Jurnal Teknologi Terapan, 2025)
Sambal pecel powder is one of the food innovations of sambal pecel paste which is made into powder through drying process. The purpose of this study was to determine the type of substitute peanuts and its comparison with peanuts that can produce chili powder with the lowest fat content and the best organoleptic characteristics. The factors of the research were substitution of cowpea, red kidney bean, and mung bean and their ratios were 30:70, 40:60, and 50:50. From 9 samples with 3 different types of peanut and different comparisons, it was found that sambal pecel powder with a combination of mung bean substitution and the ratio (40:60) produced sambal pecel with the lowest fat content. Sambal pecel powder with a combination of mung bean substitution gave good results in terms of all the analysis performed, but for organoleptic results, sambal pecel powder with a combination of kidney bean substitution was most liked by panelists. Mung bean powder has another potential to be used as a substitute ingredient because it contains higher protein than kidney bean and cowpea.